Accurate satellite measurements of greenhouse gases.
The lack of suitable laser sources has been one of the main challenges in space missions designed to measure sources and sinks of greenhouse gases. However, a new generation of all-semiconductor laser sources promises optical instruments with the required measurement accuracy.